Ionic chromophores Xep+ (p ≤ 4) in multishell rare-gas clusters Xem(NF3)kNe7500 (m, k≤ 100) studied with fluorescence spectroscopy: Clusters - Kanaev, A.; Museur, L.; Laarmann, T.; Möller, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We have studied fluorescence spectra of small Xem and Xem(NF3)k clusters (m, k ≤ 102) embedded in large host Ne7500 clusters, excited with SR excitation in the VUV spectral region above the Xe+(2P1/2) atomic limit. The IR emission bands due to ionic chromophores Xep+ (p = 2, 3, 4) as well as UV (B–X) and visible (C–A) bands due to desorbed Xe+F– excimer molecules have been observed. The triatomic Xe2F excimer emission has only been observed under low-energy excitation close to the lowest xenon exciton absorption band. A competition between ionic and charge-transfer reaction channels is followed as a function of the cluster sizes m and k.